P136 Endoscopic ultrasound: a highly effective tool in the investigation of lymphadenopathy of unknown cause. (19th June 2022) - Ahmed, Wafaa; Joshi, Deepak; Prachalias, Andreas; Patel, Ameet; Harrison, Phillip; Menon, Krish; Srinivasan, Parthi; Devlin, John; Reffitt, David
Abstract : Introduction: Endoscopic ultrasound (EUS) guided tissue acquisition is an indispensable tool in the diagnostic pathway of upper GI and hepatobiliary cancer. We sought to assess its utility in guiding patient management in patients presenting with lymphadenopathy of unknown cause. Methods: Consecutive patients with lymphadenopathy undergoing EUS guided lymph node sampling were retrospectively analysed. Recorded variables included patient demographics, procedural characteristics, histological findings and patient management. Results: 90 episodes (males n=51, 57%) were identified over a ten-year period. Median age at EUS was 62 years old (range 13-88 years old). Median size of lymph node sampled was 20mm (range 6-71mm), with a median of 2 passes (range 1-4). A 22 G needle was used in 62 (68.89%) of cases. The majority of lymph nodes sampled were from the peri-pancreatic area (n= 50, 56%), followed by peri-hepatic (n=15, 17%), celiac (n= 14, 16%), para-esophageal (n=4, 4.%), peri-gastric (n=3, 3%), mediastinum (n=2, 2%) and para-duodenal (n=2, 2%). The final diagnosis were benign lymphadenopathy (n= 31, 34%) followed by adenocarcinoma (n=23, 26%), lymphoma (n=6, 7%), tuberculosis (TB) (n=5, 6%), sarcoidosis (n=5, 6%), and neuroendocrine tumour (n=5, 6%). There was insufficient tissue for histological diagnosis in 15 (17%) cases. Sensitivity for malignancy was 78% with a specificity of 100%. Sensitivity for inflammatory disorders was 88%. All the cases with TB had a positive diagnosis. There were no complications associated with EUS guided sampling. Conclusions: EUS is a highly safe and effective method of tissue acquisition in patient presenting with unexplained lymphadenopathy.